Developing Visual Haptic Application For Learning Jawi Handwriting Skills - Maizan, Mat Amin (2013)
The visual haptic approach is considered as a very promising potential to aid primary school pupils in teaching and learning method of Jawi handwriting skills. An effort to help pupils in learning Jawi handwriting skills has prompted this study. This paper explores the related literatures and previous studies on visual haptic in handwriting. It also summarizes the findings of the preliminary study on the current approach of teaching and learning of Jawi handwriting skills, and the potential of the visual haptic approach in the Malaysian educational setting. This paper also discusses two main phases involved in this study, which are the development and the usability testing of Visual Haptic Jawi (HV-Jawi). The proposed conceptual framework hopefully can be a guide in developing a visual haptic application such as HV-Jawi.